An Analytical View to Environmental Quality of Life in the European Union Countries - Huttmanová, Emília; Novotný Roman; Valentiny, Tomáš (European Journal of Sustainable Development, 2019)
Quality of life and health is very closely linked to the environmental quality. However, the environmental quality is not only perceived as a determinant of quality of life, but it is an internal part of (sustainable) development, in terms of the green growth concept, at these days. The concept of green growth is one of the newer ways to ensure economic and social development in the context of sustainable development. Economic and social development, as well as ensuring and preserving the environmental quality, has its important place in the green growth concept. Green growth requires a new view on management of economic and social development. This article is focused on the evaluation of interregional disparities in selected areas of sustainable development. The aim of the paper is to evaluate the environmental quality of life in European Union countries using the selected indicators of green growth in the context of sustainable development. Keywords: Environment, Quality of life, Green growth, Indicators, European Union countries